Respuesta :
First, simplify. Combine like terms
10x - 3x = 7x
7x + 1 = x + 4
Isolate the x. Subtract x from both sides, and 1 from both sides
7x (-x) + 1 (-1) = x (-x) + 4 (-1)
7x - x = 4 - 1
Simplify
6x = 3
Isolate the x. Divide 6 from both sides
6x/6 = 3/6
x = 1/2
1/2, or 0.5 is your answer for x.
hope this helps
-3x + 1 + 10x = x + 4
7x + 1 = x + 4
-x -x
6x + 1 = 4
-1 -1
6x=3
÷6 ÷6
x= 0.5
sorry it's confusing im only good at math not explaining
7x + 1 = x + 4
-x -x
6x + 1 = 4
-1 -1
6x=3
÷6 ÷6
x= 0.5
sorry it's confusing im only good at math not explaining